PENGETAHUAN KEBERSIHAN GENETALIA EKSTERNA DENGAN KEJADIAN FLUOR ALBUS - Rehana Rehana; Fariha Nuzulul Hinisa; Nurul Komariah (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2022)
Background: Vaginal discharge is one of the reproductive health problems that many young women complain about. there are still many young women who do not understand about genital hygiene and think that vaginal discharge is trivialMethod: The population of this study were all high school students of class XI as many as 203 students. The research sample was Class XI students at SMA Palembang who met the inclusion and exclusion criteria. The sampling technique is simple random sampling, the number of samples is 74 people. Cross Sectional Research Design. The research instrument was in the form of a biodata questionnaire, knowledge and incidence of fluor albus. The questionnaire was valid and reliable. Data analysis with frequency distribution and Chi-Square.Result: Based on the results of the above calculations with the results of Chi Square analysis test with a confidence level of 0.05 obtained p-Value = (0.002≤0.05) then Ho is rejected, which means that there is a relationship between knowledge of external genital hygiene and the incidence of vaginal discharge.Conclusion : Students' knowledge about external genital organ care is still lacking. There is a relationship between knowledge of external genitalia care and the incidence of fluor albus.